Designing a Learner-Centered Entrepreneurship Curriculum to Empower MSMEs in Cirebon through Institutional and Ecosystem Alignment - Izzatunisaa Ainunhusna; Sonny Rustiadi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to design a learner-centered curriculum that supports the empowerment of micro, small, and medium enterprises in Cirebon. It responds to the need for academic programs that connect more closely with real challenges faced by MSMEs in the region. Using a qualitative method, the research explores both external and internal conditions, including the ecosystem environment, institutional readiness, and stakeholder roles. Several analysis tools are used such as PESTLE, the Entrepreneurship Ecosystem Model, Service Quality Model, Value Proposition Canvas, and stakeholder mapping. The study also involves interviews with local MSMEs and the head of the Cirebon MSME department. From these insights, a flexible and collaborative curriculum framework is proposed. It puts students at the center of the learning process while ensuring direct involvement with MSMEs and community actors. The curriculum is designed to be practical, responsive, and aligned with national education standards, aiming to build strong collaboration between SBM ITB and the Cirebon ecosystem.